THE INFLUENCE OF HOSPITAL BRAND IMAGE ON PATIENT'S DECISION TO CHOOSE HOSPITAL: LITERATURE REVIEW - Maulana, Akhada; Ayuningtyas, Dumilah (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2023)
People nowadays with different characteristics are very selective when choosing medical services. Hospitals as service providers are expected to have a good brand image which is the patient's perception of a brand. It is built by trust in care and knowledge about the hospital. The hospital's brand image makes patients recognize and differentiate them from others. Patient selection of health care facilities is a complex process. The brand image expected to had a direct effect on hospital selection. This article explains the influence of hospital brand image on patients' decisions to choose a hospital. The method used is a literature review study and sources from online academic media such as Mendeley. Studies related to the field of health services and searched for using valid keywords. We found 48 articles, and after evaluation, eight selected articles were included in this study. From various studies, we found that brand image positively impacts patients' decisions in choosing a hospital. A hospital's brand image will influence patient perceptions of service quality. The social aspect and marketing communication strategy have proven to be excellent induction processes for establishing a brand image in the minds of consumers.